Implementasi Aplikasi Perpustakaan Berbasis Website Menggunakan Framework Codeigniter 4 di Sekolah Dasar - Nugroho, Aventura Suryo; Mujiyono, Sri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
The use of information technology is increasingly essential in data processing and storage, including library management in schools. The library at SD Negeri Candirejo 02 still applies a manual system for recording borrowings, returns, and book collection management. This condition creates several problems such as delays in data retrieval, recording errors, and inefficiency in library services. This study aims to implement a web-based library application to improve the effectiveness and efficiency of data management at SD Negeri Candirejo 02. The research method employed the waterfall model, which consists of system requirements analysis, system design, implementation, testing, and maintenance. The application was developed using PHP programming language with the CodeIgniter 4 framework and MySQL as the database, and it was equipped with a QR code scanning feature. The implementation results show that the application, named PerpusKu, can assist library staff in managing borrowing, returning, member data, book categories, book racks, and fine reports more quickly and accurately. Testing using black-box methods indicated that all features functioned as expected. Therefore, this application can serve as an effective solution for elementary school libraries in overcoming the limitations of manual systems and supporting sustainable collection management.